Disseminated lymphoblastic lymphoma in children and adolescents: results of the COG A5971 trial: a report from the Children's Oncology Group. (24th July 2013) - Termuhlen, Amanda M.; Smith, Lynette M.; Perkins, Sherrie L.; Lones, Mark; Finlay, Jonathan L.; Weinstein, Howard; Gross, Thomas G.; Abromowitch, Minnie
Summary: The Children's Oncology Group's A5971 trial examined central nervous system (CNS) prophylaxis and early intensification in paediatric patients diagnosed with CNS‐negative Stage III and IV lymphoblastic lymphoma. Using a 2 × 2 factorial design, the study randomized patients to Children's Cancer Group (CCG) modified Berlin‐Frankfurt‐Muenster (BFM) acute lymphoblastic leukaemia (ALL) regimen with intensified intrathecal (IT) methotrexate (MTX) (Arm A1) or an adapted non‐Hodgkin lymphoma/BFM‐95 therapy with high dose MTX in interim maintenance but no IT‐MTX in maintenance (Arm B1). Each cohort was randomized ± intensification (cyclophosphamide/anthracycline) (Arms A2/B2). For the 254 randomized patients, there was no difference in 5‐year event‐free survival (EFS) for the four arms: Arm A1, 80% [95% confidence interval (CI) 67–89%] and Arm A2, 81% (95% CI 69–89%); Arm B1, 80% (95% CI 68–88%) and Arm B2, 84% (95% CI 72–91%). The cumulative incidence of CNS relapse was 1·2%. Age <10 years and institutional imaging response at 2 weeks was associated with improved outcomes ( P  < 0·001 and P  = 0·014 for overall survival). CNS positive patients ( n  = 12) did poorly [5‐year EFS of 63% (95% CI 29–85%)]. For CNS‐negative patients, there was no difference in outcome based on CNS prophylaxis (IT‐MTX versus HD‐MTX) or with intensification.